Simulation of multiple mobile robots using JMonkey Engine - Tang, Shuen Cherng (2016)
Nowadays simulation in the robotics field is very important before the implementation of the real mobile robot. Due to the advanced robotics system are getting more complex nowadays, simulation has become a valuable tool which helps researchers in development industry and testing robot control algorithm. JMonkey Engine is a game development engine chosen as the robot simulator because it contains the accuracy in physics simulation, high-quality rendering system, open source, and multiplatform which are essential components in forming a good simulator. The project consists of two parts whereby the main part is to develop a server-clients networked multiple mobile robot simulations. The main purpose of this JmeSim networking simulation is to serialize the mobile robot’s position by sending the robot’s position message to the server subsequently the server will broadcast the state information to all connected clients and update the scene of the simulation. On the other hand, the subpart for this project is to design a virtual slider gripper with a function of gripping objects and travelling to the desired destination without dropping the object.